114k views
5 votes
Help mathmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmm

Help mathmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmmm-example-1

1 Answer

2 votes

Answer:B

f(x)-g(x) =(f -g)(x)= 3^x - 2x + 14

Explanation:

If f(x) = 3^x + 10 and g(x) = 2x-4

Find (f-g)(x)

This simply means or implies that

f(x)-g(x)

Factorizing (x) as the common factor

(x)(f-g) = (f-g)(x). They mean the same thing and can be used interchangeably.

So (f-g)(x) = f(x)-g(x)

[f(x) = 3^x + 10] - [g(x) = 2x-4]

= 3^x + 10 - (2x-4)

= 3^x + 10 - 2x+4

= collect like terms ( terms containing x together and the constants together)

3^x - 2x +4 + 10

= 3^x - 2x + 14

So the final answer is B

= 3^x - 2x + 14

User Ludwig
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.